Evaluasi persepsi penerapan penumbuhan unit usaha complete feed sapi potong (Studi kasus di kelompoktani Kabupaten Pasuruan) - Yudi Rustandi; Ismulhadi Ismulhadi; Mirna Silviani (Universitas Sebelas Maret, 2021)
Objective: Members of farmer group are required to be more adaptive to change in livestock technology development, one of which is the innovation of growing animal feed business units as part of the production unit of farmer groups. This study aimed to determine the suitability level of the extension program and the perception of group members in the application of growing beef cattle complete feed business units.Methods: This study is an evaluation study with a formative and summative evaluation model. The objects of evaluation are 1) Suitability of extension programs and 2) Perceptions of farmer group members on the growth of beef cattle complete feed business units. Respondents were 38 members of farmer groups. The instrument in the form of a questionnaire (likert scale) test through validity and reliability tests. Data analysis used quantitative descriptive analysis and T score.Results: The results of the evaluation, the members of the farmer groups assessed: 1) The extension program was appropriate because; material aspect T score> 39.92, media aspect T score> 19.95, and method aspect T score> 24.92, 2) Innovation attributes, namely: a) relative advantage, can be tried (trialability), and observability, as many as 38 people or 100% expressed a positive perception, b) the level of compatibility, as many as 36 people or 94.40% expressed a positive perception, c) the level of complexity, as many as 37 people or 97, 36% expressed a positive perception.Conclusions: Farmers' group members assess that the extension program is appropriate, and their perceptions are also positive on efforts to grow beef cattle complete feed business units.